Ethnobotany of Medicinal Plants from the Malay People in Tanjung Village, Bunguran District, Northeastern District of Natuna Regency - Asmita Asmita; Riza Linda; Dwi Gusmalawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The use of plants in traditional medicine has been used out by people in the Kepulauan Riau. However, knowledge about the use of plants in traditional medicine by the Malay people in Tanjung Village, Northeast Bunguran District, Natuna Regency, has never been documented. The aim of this study is to identify the species of plants and plant parts that are used, to learn how to prepare and use medicinal plants, and to evaluate the importance of citation frequency and informant agreement elements in Tanjung village’s traditional medicine. The research was carried out by conducting semi-structured interviews, and continued with a discussion of 13 respondents who were determined by snowball sampling. The data collected includes: the plant species and families, the component used, the processing method, the usage method, and useg. Also, the informant agreement factor and the frequency of citations/mentions of each medicinal plant (%) were determined. The results showed that the people in Tanjung Village used 72 species of plants in traditional medicine. Fabaceae and Zingiberaceae are the dominant plant families reported by respondents as medicinal plants. Generally, the people in Tanjung Village use more of the leaves (46.67%) for use as medicine, the processing method is by boiling (33.3%) and the method of use is by drinking it (58.2%).